Analysis Of The Social Influence Of The Outside Society On The Changes In The Life Style Of Baduy Luar Tribe - Jamaludin, Anang; Bungsu, Intan Putri; Aisyah, Fatma; Khoiriyah, Eneng Liah; Khairunnisa, Iim; Fithrotunnisa, Eka Dewi (Educativo: Jurnal Pendidikan, 2023)
This research aims to conduct a quantitative analysis of the social influence of outsiders on the lifestyle changes of the Outer Baduy community. The Outer Baduy community is known for maintaining their distinctive traditions and lifestyle. However, globalization and interaction with outside society can have a significant impact on their lifestyle. This research method adopts a quantitative approach by using a research instrument in the form of a questionnaire distributed to members of the Outer Baduy community who have interacted with the outside community. Data collection was conducted in the settlement area of Outer Baduy and its surroundings. The collected data were analyzed using statistical techniques such as regression to identify the relationship and significance level of the social influence of the outside community on lifestyle changes. The result shows that there is a significant relationship between interaction with outside community and lifestyle change of Outer Baduy community. Factors such as education, social media, and outside cultural influences play an important role in this change. While there are positive changes in lifestyle such as increased access to education, there are also aspects that raise concerns, such as the potential loss of traditional values. This research contributes to the understanding of quantitative social impact on the Outer Baduy community due to interaction with the outside community. The implication of this research can be used as the basis for developing a more targeted policy in maintaining the sustainability of culture and traditional values of the Outer Baduy community, while utilizing the potential positive changes that may occur in the process of interaction with the outside community.